A Novel Chitosan-Based Fluorescence Chemosensor for Selective Detection of Fe (III) Ion in Acetic Aqueous Medium - Pournaki, Mehrad (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
An ecofriendly chitosan-based urolithin fluorescence (Uro-m-Ch) optical sensor was successfully synthesized and characterized by Fourier transform infrared spectroscopy. According to the FTIR results, the chitosan characteristic peaks were observed around 3500−3300 cm−1, 1656 cm−1, 1587 cm−1 and 1179 cm–1 which are attributed to hydroxyl, amide I, N–H deformation and C–O–C stretching, respectively. The Uro-m-Ch featured the representative peaks of chitosan and the lactone carbonyl stretching of the urolithin. The Uro-m-Ch demonstrated fluorescence character in the presence of 1% (v/v) CH3COOH/H2O solution with a maximum excitation wavelength (λmax) within 290–330 nm and λmax emission spectrum at 430 nm with Stokes shift of 100 nm without the target metal ion. Notably, in the presence of iron (III) concentration from 0.10 to 0.080 mM; Uro-m-Ch exhibited a maximum wavelength emission at 420 nm with a decreasing trend in fluorescence intensity. During the selectivity and interference studies, Uro-m-Ch demonstrated a remarkable quenching effect only with Fe3+ ion among various mono- and multivalent metal ions. Considering the fluorescence responses of the Uro-m-Ch, its sensing mechanism towards Fe3+ ion was attributed to intramolecular energy/electron transfer between the lactone group of the urolithin and/or the hydroxyl moiety of the chitosan backbone and the iron (III) ion. Results herein confirmed that Uro-m-Ch is rapid, selective and sensitive towards Fe3+ ion detection in aqueous acetic solution. Keywords: Chitosan, Urolithin B, Iron (III) ion, Fluorescent, Chemosensor, Selective detection

ÖZ: Çevre dostu kitosan bazlı ürolitin floresan (Uro-m-Ch) optik sensör başarıyla sentezlendi ve Fourier dönüşümü kızılötesi spektroskopisi ile karakterize edildi. FTIR sonuçlarına göre, kitosanın karakteristik zirveleri olan hidroksil, amid I, N–H deformasyonu ve C–O–C uzaması sırasıyla 3500−3300 cm−1, 1656 cm−1, 1587 cm−1 ve 1179 cm–1 dalga numaralarında gözlenmiştir. Uro-m-Ch, kitosanın temsili zirvelerine ve ürolitinin lakton karbonil gerilmesine sahipti. Uro-m-Ch, %1 (v/v) CH3COOH/H2O çözeltisinin varlığında 290-330 nm arası maksimum uyarma dalga boyu (λmax) ve hedef metal iyonu yokluğunda 100 nm Stokes kayması ile 430 nm'de λmax emisyon spektrumu olan bir floresan karakter sergilemiştir. Özellikle, 0.10 ila 0.080 mM arasında demir (III) konsantrasyonunun varlığında; Uro-m-Ch, floresan yoğunluğunda azalan bir trendle 420 nm'de maksimum dalga boyu emisyonu sergiledi. Seçicilik ve engelleme çalışmaları sırasında, Uro-m-Ch, çeşitli tek ve çok değerlikli metal iyonları arasında yalnızca Fe3+ iyonu ile dikkate değer bir söndürme etkisi göstermiştir. Uro-m-Ch'nin floresan tepkileri göz önüne alındığında, Fe3+ iyonuna yönelik algılama mekanizması, ürolitinin lakton grubu ve / veya kitosan omurgasının hidroksil kısmı ile demir (III) iyonu arasındaki molekül içi enerji / elektron transferine atfedildi. Buradaki sonuçlar, Uro-m-Ch'nin hızlı, seçici ve sulu asetik çözelti içinde Fe3+ iyonu tespitine karşı duyarlı olduğunu doğruladı. Anahtar Kelimeler: Kitosan, Ürolitin B, Demir (III) iyonu, Floresan, Kemosensör, Seçici tespit
Doctor of Philosophy in Chemistry. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Chemistry, 2021. Co-Supervisor: Assoc. Prof. Dr. Hayrettin Ozan Gülcan and Supervisor: Prof. Dr. Mustafa Gazi.
Keywords: Chemistry; Chitosan; Chitosan; Urolithin B; Iron (III) ion; Fluorescent; Chemosensor; Selective detection